2017
DOI: 10.1038/s41598-017-10476-x
|View full text |Cite
|
Sign up to set email alerts
|

Single, but not dual, attention facilitates statistical learning of two concurrent auditory sequences

Abstract: When we are exposed to a novel stimulus sequence, we can learn the sequence by extracting a statistical structure that is potentially embedded in the sequence. This mechanism is called statistical learning, and is considered a fundamental and domain-general process that is innate in humans. In the real-world environment, humans are inevitably exposed to auditory sequences that often overlap with one another, such as speech sound streams from multiple speakers or entangled melody lines generated by multiple ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…There is considerable evidence that the reproduction of a time interval depends significantly on several factors, including stimuli, age, gender, learning abilities, and cognitive function ( Szelag, 1997 ; Szelag et al, 1998 , 2002 , 2004a , b ; Kanabus et al, 2004 ). The cerebral cortex is a learning machine that can work regardless of attention and domain of learning ( Daikoku et al, 2012 , 2014 , 2015 , 2016 , 2017a , b , c ; Koelsch et al, 2016 ; Daikoku and Yumoto, 2017 ; Daikoku, 2018 ), and that can be developed by cognitive and motor learning throughout life ( Merzenich et al, 1996 ). Szelag et al (1998) suggested that the prefrontal cortex, which is responsible for the developmental effect, also plays an important role in temporal processing, and is involved in working memory up to around 3 s. Previous studies report that males and older individuals tend to outperform women and younger individuals on perception tests related to temporal processing, respectively ( Linn and Petersen, 1985 ; Szelag et al, 1997 , 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that the reproduction of a time interval depends significantly on several factors, including stimuli, age, gender, learning abilities, and cognitive function ( Szelag, 1997 ; Szelag et al, 1998 , 2002 , 2004a , b ; Kanabus et al, 2004 ). The cerebral cortex is a learning machine that can work regardless of attention and domain of learning ( Daikoku et al, 2012 , 2014 , 2015 , 2016 , 2017a , b , c ; Koelsch et al, 2016 ; Daikoku and Yumoto, 2017 ; Daikoku, 2018 ), and that can be developed by cognitive and motor learning throughout life ( Merzenich et al, 1996 ). Szelag et al (1998) suggested that the prefrontal cortex, which is responsible for the developmental effect, also plays an important role in temporal processing, and is involved in working memory up to around 3 s. Previous studies report that males and older individuals tend to outperform women and younger individuals on perception tests related to temporal processing, respectively ( Linn and Petersen, 1985 ; Szelag et al, 1997 , 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies of word segmentation detected SL effects on the N400 component [ 43 , 46 , 88 , 89 , 93 , 94 , 105 ], which is generally considered to reflect a semantic meaning in language and music [ 106 , 107 , 108 ], auditory brainstem response (ABR) [ 96 ], P50 [ 41 ], N100 [ 94 ], mismatch negativity (MMN) [ 40 , 44 , 98 ], P200 [ 46 , 89 , 105 ], N200–250 [ 44 , 47 ], and P300 [ 83 ] have also been reported to reflect SL effects ( Table 1 ). In addition, other studies using Markov models also reported that SL is reflected in the P50 [ 14 , 36 , 37 ], N100 [ 10 , 14 , 32 , 35 ], and P200 components [ 35 ]. Compared with later auditory responses such as N400, the auditory responses that peak earlier than 10 ms after stimulus presentation (e.g., ABR) and at 20–80 ms, which is around P50 latency, have been attributed to parallel thalamo–cortical connections or cortico–cortical connections between the primary auditory cortex and the superior temporal gyrus [ 109 ].…”
Section: Neural Basis Of Statistical Learningmentioning
confidence: 99%
“…Recent neural studies have demonstrated that SL of speech, pitch, timbre, and chord sequences can be performed and reflected in ERP/ERF [ 10 , 36 , 37 , 40 , 46 ]. Furthermore, the brain codes statistics of auditory sequences as relative information, such as relative distribution of pitch and formant frequencies, which could be used for comprehension of another sequential structure [ 10 , 32 ], suggesting that SL is ubiquitous and domain-general.…”
Section: Clinical and Pedagogical Viewpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…A tone with a higher transitional probability of sequences in a musical score may be one that a composer is more likely to choose compared to other tones with lower transitional probability [ 20 23 , 58 60 ]. Thus, the transitional probability matrix calculated from music may represent the characteristics of a composer’s statistical knowledge by which a forthcoming tone is implicitly defined.…”
Section: Discussionmentioning
confidence: 99%